Parental rights to maintenance under Islamic law - Hj Ibrahim, Badruddin (2007)
The relationship between parents and children is of a profound and special one. This is due to the fact that such relationship is based on blood and lineage relationship. The relationship gives rise to various duties and rights particularly the rights of children or duties of parent toward their children, for instance, right of children to protection, custody, guardianship and maintenance. These rights of children are basically recognized by every legal system of the world. The question is whether such relationship reflects only one-side responsbility i.e. the responsibility of parent. Do children also owe a legal duty toward their parent? This paper seeks to examine one of the significant reghts of parent concerning maintenance under the jurisdiction of Islamic law, whether a parent is entitled to such right. In case if they are entitled, it follows that whether such right is legally enforceable in the court of law or merely an ethical recommendation. In additional, it examines the circumstances and conditions of the entitlement of parent to maintenance. It also examines the position of current Islamic law in Malaysia as to what extent such law emphasizes and provides significant provisions on just and equitable law to protect parents' rights to maintenance. Finally, the paper will provide, where necessary, comments and suggestions on the issue.